Legal Protection for MSMEs in Facing Business Competition - Chairus Suriyat; M. Salim; Bambang Sutejo (Outline Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the Indonesian economy, but often face major challenges in business competition, especially with large companies. Unfair business competition practices, such as monopolies, predatory pricing, and cartels, often harm MSMEs. This study aims to analyze the legal protection available to MSMEs in facing business competition, the effectiveness of existing regulations, and obstacles in their implementation. The research method used is a normative approach with an analysis of applicable laws and regulations, as well as an empirical approach through case studies related to business competition policies in Indonesia. The results of the study show that although there are regulations such as Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and Law Number 20 of 2008 concerning Micro, Small, and Medium Enterprises, the implementation of legal protection still faces various obstacles. Lack of socialization of regulations, low legal awareness among MSMEs, and limitations in supervision by the Business Competition Supervisory Commission (KPPU) are the main factors that hinder the effectiveness of legal protection. Therefore, reforms are needed in business competition policy, increasing legal literacy for MSMEs, and synergy between the government, KPPU, and MSME associations to create a fairer and more competitive business ecosystem